-5n-10=-(8n-1)-8n

Simple and best practice solution for -5n-10=-(8n-1)-8n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5n-10=-(8n-1)-8n equation:


Simplifying
-5n + -10 = -1(8n + -1) + -8n

Reorder the terms:
-10 + -5n = -1(8n + -1) + -8n

Reorder the terms:
-10 + -5n = -1(-1 + 8n) + -8n
-10 + -5n = (-1 * -1 + 8n * -1) + -8n
-10 + -5n = (1 + -8n) + -8n

Combine like terms: -8n + -8n = -16n
-10 + -5n = 1 + -16n

Solving
-10 + -5n = 1 + -16n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '16n' to each side of the equation.
-10 + -5n + 16n = 1 + -16n + 16n

Combine like terms: -5n + 16n = 11n
-10 + 11n = 1 + -16n + 16n

Combine like terms: -16n + 16n = 0
-10 + 11n = 1 + 0
-10 + 11n = 1

Add '10' to each side of the equation.
-10 + 10 + 11n = 1 + 10

Combine like terms: -10 + 10 = 0
0 + 11n = 1 + 10
11n = 1 + 10

Combine like terms: 1 + 10 = 11
11n = 11

Divide each side by '11'.
n = 1

Simplifying
n = 1

See similar equations:

| y=(x-2)-1 | | -(30)-(10)-43= | | 25200*(1/9) | | 80=1.8C+32 | | -255=-15k | | 10h=2(4h+13) | | 3a+9-6=21 | | 9.95m=m | | -3(x+5)=-3x-15 | | -18+2(j-12)=-12j | | 25200*(1/10) | | 4.95m+49.95=m | | -0.75x-2=0.25x | | y-6=-5/4(x+1) | | 6y=-3x(2)-4 | | (x+2)*3=(x-10)*7 | | 6(7g-16)=4(6g+12) | | 52=p | | -8(-6x+6)=-4x+4 | | -5v-38=-3(5v-4) | | 25200(1/10) | | 5x+83=29 | | -48-6x=(-3x)+12 | | 8.3+6x=8.6 | | 6=-3(2)-4 | | 31=w/3+31 | | z2=25/49 | | -9(-4)+7=25+2(5--7) | | 3.6x=1.6x+24 | | 16.65-8.5c+17.66=11.87-9.7c | | u=2(8n+30)+5(n+1) | | P=2(100)+2(200) |

Equations solver categories